Simplifying the Bureaucracy Through Transaction Cost Theory (Jurnal Bina Praja, 2024)
The policy of simplifying the bureaucracy aims to simplify, but in its preparation, it produces many regulations that also cost a lot of money. The Ministry of Finance publishes an average cost incurred for the preparation of one ministerial regulation of up to Rp232 million, not including other costs that do not look like the formulation time. This study analyzes transaction costs in bureaucratic simplification and identifies government efforts to improve transaction cost efficiency. This study uses mixed methods and explanatory sequential analysis to analyze the efforts made by the Government. This study, conducted in 2021-2022, combines qualitative and quantitative methods. The qualitative method of data collection uses in-depth interviews and focus group discussions. While the quantitative method uses a questionnaire. The study results show that the Government has made various efforts to improve the efficiency of transaction costs. Still, various policies that have been prepared to overcome bureaucratic inefficiencies through bureaucratic simplification tend to increase formalization and increase costs. These various government efforts cannot be solely assessed using an economic perspective. Based on a study conducted by the University of Chicago, government bureaucracy will never be truly mathematically efficient because of the way it works, unlike the private sector. The impact of bureaucratic simplification is a long-term benefit, considering that this has an effect on governance that has not been calculated. Inefficiency or large costs incurred by the Government today will be an investment in improving governance in the future.
Keywords: Transaction Cost Theory; Bureaucratic Simplification; Administrative Reform; Efficiency